Two Cases of Very-Late-Onset Neuromyelitis Optica Spectrum Disorder (NMOSD) in Patients over the Age of 80 - Fujiwara, Shunya (Case Rep Neurol, 2020)
We report two cases of very-late-onset neuromyelitis optica spectrum disorder (NMOSD) in patients over the age of 80 with transverse myelopathy as the initial manifestation. In both cases, the patients presented with paraplegia and sensory, bladder, and rectal disturbances. Thoracic magnetic resonance imaging showed longitudinal high-intensity signals on a T2-weighted image. The patients received high-dose methylprednisolone. Their serum was positive for anti-AQP4 antibody (cell-based assay) during the clinical course. They were diagnosed with NMOSD and treated with immunoadsorption, plasmapheresis, and followed up with daily prednisolone. Very-late-onset NMOSD in patients over the age of 80 has only rarely been reported. The present cases suggest that NMOSD should be considered for elderly patients presenting with transverse myelitis. Early diagnosis and treatment are important.